Louise Bryant and the Russian Revolution - Farrow, Lee A. (Journal of Russian American Studies, 2017)
This article explores the life and contributions of Louise Bryant, an American journalist and activist who documented the Russian Revolution of 1917. Bryant witnessed key events alongside John Reed and provided unique insights into the revolution's social and political transformations. Her work, Six Red Months in Russia, contrasts with Reed's by emphasizing personal commentary and vivid depictions of revolutionary life. Despite her contributions, Bryant's legacy has been overshadowed by Reed and broader gender biases. The article reexamines Bryant's role as an observer of history, highlighting her unique perspective as a suffragist and socialist and the relevance of her work in understanding the Russian Revolution's impact on Russian-American relations and global socialism.